Rapid solidification of alloys. (1st September 2004) - Baricco, M.; Bosco, E.; Olivetti, E.; Palumbo, M.; Rizzi, P.; Stantero, A.; Battezzati, L.
This paper reviews some applications of rapid solidification processing of alloys. With reference to original work of the authors, the production and properties of amorphous alloys, mainly iron based, of nanocrystalline aluminium alloys and of granular materials are described. A section is devoted to the latest advancement of thermodynamic modelling of metastable systems using CALPHAD softwares.